Influence of Exogenous Epigallocatechin Gallate Addition on Physicochemical Properties of Buckwheat Flour and Eating Quality of Buckwheat Wantuo - Di WU; Ruhui XIA; Hong MA; Xiaozhi TANG (Shipin gongye ke-ji, 2023)
This research aims to ameliorate the eating quality of Chinese traditional starch-based food: buckwheat Wantuo via the addition of exogenous polyphenol. The mixed flour (MF) was prepared by adding various amount of Epigallocatechin gallate (EGCG) to common buckwheat flour. The influence of addition amount on physicochemical properties (like color, hydration and pasting) of MF and eating quality (like total phenol content, antioxidant activity and digestibility) of buckwheat Wantuo (BWT) were investigated. The results clearly showed that the color of MF turned dark red while the water solubility index and setback value were increased and decreased with increasing EGCG concentration, respectively. Meanwhile, the number of pores in MF gel section was significantly increased, whereas the pore size was decreased. The ordered structure and relative crystallinity as well as the cohesiveness and resilience of BWT samples were decreased gradually, while the total phenols content and antioxidant activity of BWT samples were significantly increased. Remarkably, the starch digestibility was significantly decreased. Sensory attributes of texture and color were insignificant with the addition of EGCG, whereas the taste score was affected. When the addition amount of EGCG was 1%, setback value of MF was decreased about 16.30%; rapidly digestible starch of BWT was decreased about 14.4%, while total phenolic compound content and pGI value of BWT were increased and decreased to 534.04 mg GAE/100 g and 61.72, respectively. At this point, the sensory score was 78.00 which was the highest in BWT samples. The results above indicated that the addition of EGCG can significantly influence the physicochemical properties of MF and can help ameliorate the antioxidant activity and digestibility of BWT.